2014
DOI: 10.1051/0004-6361/201424677
|View full text |Cite
|
Sign up to set email alerts
|

Are compact groups hostile towards faint galaxies?

Abstract: Aims. The goal of this work is to understand whether the extreme environment of compact groups (CGs) can affect the distribution and abundance of faint galaxies around them. Methods. We performed an analysis of the faint galaxy population in the vicinity of compact and normal groups. We built a light-cone mock galaxy catalogue constructed from the Millennium Run Simulation II plus a semi-analytical model of galaxy formation. We identified a sample of CGs in the mock catalogue as well as a control sample of nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Despite the relative proximity, there have been no detailed studies on its LSB dwarf galaxy population, as most attention has been paid to the group's bright and/or ultra-compact dwarf (UCD) (de Ribeiro et al 1994;Da Rocha et al 2011), and giant galaxies. This avenue of study is ripe for investigation, as other HCGs have been shown to host faint dwarfs (Campos et al 2004;Carrasco et al 2006;Krusch et al 2006;Konstantopoulos et al 2013), which are to be expected from theoretical considerations, despite the dynamically more hostile environments in these systems (Zandivarez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative proximity, there have been no detailed studies on its LSB dwarf galaxy population, as most attention has been paid to the group's bright and/or ultra-compact dwarf (UCD) (de Ribeiro et al 1994;Da Rocha et al 2011), and giant galaxies. This avenue of study is ripe for investigation, as other HCGs have been shown to host faint dwarfs (Campos et al 2004;Carrasco et al 2006;Krusch et al 2006;Konstantopoulos et al 2013), which are to be expected from theoretical considerations, despite the dynamically more hostile environments in these systems (Zandivarez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated the incompleteness of the Hickson sample. Recently, and using similar semi-analytical tools, a new analysis of the influence of these extreme environments on their faint galaxy population has been performed by Zandivarez et al (2014b). These authors reported that when compared with suitable control group samples, the compact group environment is not hostile enough to modify the distribution and density of the faint galaxy population that resides in the group and in their surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…We identify these systems using a FoF algorithm in real space at 𝑧 = 0 using a longer linking length 𝑟 0 appropriate to obtain virialized loose galaxy groups. Following previous studies (Eke et al 2004;Berlind et al 2006;Zandivarez et al 2014), we adopt 𝑏 𝑓 = 0.14, and using the relations quoted in the eqs. 1 and 2, we compute the values of 𝑟 0 to identify the samples of FoF-LGs in each SAM.…”
Section: Global Isolation: Non-embedded Dense Systemsmentioning
confidence: 99%